Identificación de necesidades de formación continua del profesorado ante las demandas educativas del siglo XXI - Rodríguez Jiménez, Andrés; Miqueli Rodríguez, Bertha; Dávila Valdés, Yosdey (Universidad de Costa Rica, 2021)
The proposal of a pedagogical model that meets the 21st century educational demands in the University of Artemisia, Cuba, demanded the identification of training needs of the teaching staff to implement the model, which justify this research and it becomes into its aim. A quantitative methodology was used to explore the needs of continuous training in the sample of teachers selected through a survey that included open and closed questions, as well as Likert-type scaling. The results indicate that, although not in all cases, the respondents were reflexive enough to recognize in themselves the educational deficiencies, these exist; On the other hand, limitations in the methodological work as an essential training activity were evident, and the teachers surveyed identified the lack of a continuous training offer by the University. As conclusions, the results obtained through the applied instrument represent only the first stage of the process of identifying training needs, these should be enriched with university policies for the elective period, the results reports of the methodological work of the previous period, the results of the annual evaluations of teachers and of the controls to classes realized to the teachers. In addition, like any process, it must be fed and fed back with certain regularity so that its cycle is permanently updated. Regarding the applicability of the results, the deficiencies found constitute a starting point for the elaboration of a continuous training strategy that responds to the real training needs of teachers.